Functional interaction between human dorsal premotor cortex and the ipsilateral primary motor cortex for grasp plans: a dual-site TMS study. Issue 16 (7th November 2018) - Vesia, Michael; Culham, Jody C.; Jegatheeswaran, Gaayathiri; Isayama, Reina; Le, Ada; Davare, Marco; Chen, Robert
Abstract : Recent findings suggest that the dorsal premotor cortex (PMd), a cortical area in the dorsomedial pathway, is involved in grasp control. It is unclear, however, whether human PMd transfers grasp-related information to the primary motor cortex hand area (M1HAND ) during action preparation. The present study tested whether ipsilateral cortico–cortical connections between PMd and M1HAND in the left hemisphere are modulated during grasp preparation. Ten participants performed object-directed grasps and reaches with the right hand. Functional connectivity between left PMd and ipsilateral M1HAND was probed with dual-site transcranial magnetic stimulation. We found that PMd–M1HAND functional interactions were facilitated selectively for the muscles involved in the preparation of the upcoming grasps. The PMd–M1HAND interaction was facilitated for first dorsal interosseous muscle for both precision grip and whole-hand grasps and for abductor digiti minimi muscle for whole-hand grasps. We conclude that human dorsomedial PMd–M1HAND circuit encodes handgrip formation during grasp preparation.